AlCl3‐Catalyzed Intermolecular Annulation of Thiol Derivatives and Alkynes by 1, 2‐Sulfur Migration: Construction of 6‐Substituted Benzo[b]thiophenes. Issue 30 (15th August 2017) - Ramesh, E.; Guntreddi, Tirumaleswararao; Sahoo, Akhila K.
Abstract : A method for the AlCl3 ‐catalyzed intermolecular oxidative annulation of N ‐(arylthio)phthalimide derivatives with alkynes has been developed. The annulation reaction occurs at room temperature and involves the oxidative cleavage of the S–N bond and 1, 2‐sulfur migration, which leads to the construction of diverse arrays of π‐conjugated 6‐substituted 2, 3‐diarylbenzo[ b ]thiophene derivatives. Abstract : A modular strategy for the synthesis of 6‐substituted 2, 3‐diarylbenzo[ b ]thiophenes involving oxidative annulation of (arylthio)phthalimide derivatives with alkynes in the presence of AlCl3 is developed. The transformation proceeds by oxidative cleavage of the S–N bond and 1, 2‐sulfur migration and occurs at room temperature.